Economic freedom and human development: an empirical cross-country panel analysis - Silva de Paiva, Matheus; Soares, Paulo Cesar (Revista de Economia Mackenzie, 2025)
This paper investigates the relationship between economic freedom and human development, measured by the Human Development Index (HDI), using panel data from 186 countries (2017–2019). A random effects panel regression model estimates the impact of different dimensions of the Heritage Foundation’s Index of Economic Freedom (IEF) on HDI. The results show that Government Integrity and Labor Freedom have the strongest positive effects, emphasizing the importance of institutional quality and labor market flexibility. Investment Freedom and Financial Freedom also contribute positively, while Government Spending negatively affects HDI, suggesting inefficiencies in public expenditure. A robustness check confirms the structural relevance of economic freedom but indicates that short-term within- country variations in HDI are not fully explained. Future research should explore causal mechanisms, non-linear effects, and informal institutions. The findings suggest that policies fostering transparency, institutional integrity, and labor market efficiency are key to enhancing human development.